THE EFFECT OF SOCIAL ECONOMIC FACTORS ON THE MARRIAGE OF YOUNG WOMEN IN TEBAS DISTRICT CASE STUDY OF TEBAS RIVER VILLAGE - B1011131068, EVA SARI (Jurnal Pembangunan dan Pemerataan, 2017)
Tebas River Village is one of the most populous villages in all of the villages in Kecamatan Tebas. In addition, in the village are also many women who married at a young age. Therefore, a solution is needed to find out the factors that cause women to marry at a young age in Tebas River Village. This research uses descriptive method, using chi square analysis technique. The data of this study were obtained from primary data as well as direct interviews with married women at a young age regarding parental education level, parent's income level, and number of siblings in the nuclear family.               The results of this study indicate that the variables of parent education with the first married age of young married respondents in Tebas River Village were not significant, the income variable of parents with the first married age of young married respondents in Tebas River Village was not significant, the number of siblings with the age of first respondents who married young in Tebas River Village is not significant. Of the three variables did not provide a real relationship, which gives a real relationship from other factors of pregnancy before marriage that causes the female child to marry at a young age. Keywords: Marriage of young women, parental education, parental income, number of siblings.